2023
DOI: 10.3390/jcm12123922
|View full text |Cite
|
Sign up to set email alerts
|

Changing Epidemiological Patterns of Infection and Mortality Due to Hepatitis C Virus in Poland

Abstract: Introduction: Limited information is available on trends in hepatitis C virus (HCV) infection, particularly in Central Europe. To address this knowledge gap, we analyzed HCV epidemiology in Poland, considering socio-demographic characteristics, changing patterns over time, and the impact of the COVID-19 pandemic. Material and Methods: We examined HCV cases (diagnosis and deaths) reported by national registries and used joinpoint analysis to estimate time trajectories. Results: Between 2009 and 2021, there were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Throughout the COVID‐19 pandemic, the rates of hepatitis B and C were negatively correlated with the frequency of newly identified cases of SARS‐CoV‐2 infection (Table 1). The studies show that the pandemic has hampered the viral hepatitis elimination programs, especially in the first years, similar to the present research observations 64 . Data collected from various European centers demonstrated that until the end of 2020, there was a substantial decrease in new HBV and HCV outpatient consultations (by 32% and 39%, respectively) and new HBV and HCV referrals (by 38% and 49%, respectively), and HBV and HCV testing (by 30% and 11%, respectively) 65 .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Throughout the COVID‐19 pandemic, the rates of hepatitis B and C were negatively correlated with the frequency of newly identified cases of SARS‐CoV‐2 infection (Table 1). The studies show that the pandemic has hampered the viral hepatitis elimination programs, especially in the first years, similar to the present research observations 64 . Data collected from various European centers demonstrated that until the end of 2020, there was a substantial decrease in new HBV and HCV outpatient consultations (by 32% and 39%, respectively) and new HBV and HCV referrals (by 38% and 49%, respectively), and HBV and HCV testing (by 30% and 11%, respectively) 65 .…”
Section: Resultssupporting
confidence: 91%
“…The studies show that the pandemic has hampered the viral hepatitis elimination programs, especially in the first years, similar to the present research observations. 64 Data collected from various European centers demonstrated that until the end of 2020, there was a substantial decrease in new HBV and HCV outpatient consultations (by 32% and 39%, respectively) and new HBV and HCV referrals (by 38% and 49%, respectively), and HBV and HCV testing (by 30% and 11%, respectively). 65 In addition, the coverage of the first HBV vaccine dose in Polish children decreased in 2020-2022 to 97.2%-97.4% from a median level of 98.2% in 2016-2019, while the coverage of the third dose dropped to 94.9%-95.4% from a median 97.2% in the prepandemic period 32 with a median rate of new hepatitis B and C cases of 0.71-0.73 per 10 5 seen in 2023.…”
Section: Viral Hepatic Infectionsmentioning
confidence: 99%
“…Joinpoint regression analysis was performed to examine the changes associated with diagnosis and mortality during the last 17 years (2005 to 2021), allowing the detection of significant changes in trends [ 16 , 17 ]. The applied analytic method automatically identified the number and locations of joinpoints during the observation period, restricting their number to 3, resulting in up to 4 linear segments in the trend line.…”
Section: Methodsmentioning
confidence: 99%
“…A summary measured over the 2005-2021 period showed the annual average percent change (AAPC), calculated as a weighted average of partial trend APCs. The differences in examined trends of HBV infection between men and women were also examined using the Wald test [ 17 ].…”
Section: Methodsmentioning
confidence: 99%